RANCANG BANGUN ANTENA Yagi-LPDA PADA FREKUENSI 162 MHz UNTUK AIS PADA KAPAL LAUT DI PERAIRAN PULAU BALI - Okta Hadi Saputra, Putu; Ardana, I Putu; Pramaita, Nyoman (Jurnal SPEKTRUM, 2023)
The role of the sea is very important as unifying the nation and the territory of Indonesia and consequently the Government is obliged to administer governance in the field of law enforcement both against threats of violations against the use of waters and to maintain and create shipping safety and security. One way to increase the ability of the apparatus and the government to monitor and secure the territory of the Unitary State of the Republic of Indonesia is to use the AIS (Automatic Identification System) system. This AIS is used to monitor the movement of ships and provide or receive information so that actions that can harm the Unitary State of the Republic of Indonesia can be prevented. Currently, ships in Indonesia are equipped with radar, but the scope of the radar emitted by Indonesian ships is still small and small. To overcome these problems the author wants to develop a thesis with the title "YAGI-LPDA Antenna Design at 162 MHz Frequency for Automatic Identification System (AIS) on Ships in Bali Island Waters" This antenna works by being connected to the AIS system at 162 MHz frequency which able to reach the presence of ships in the waters of the Bali Strait, Lombok Strait and its surroundings. The Yagi-LPDA antenna design prototype works in accordance with the antenna design in the MMANA-GAL software, namely in the form of an SWR with a value of 1.73, a gain of 8.12 dBi, and a radiation pattern that is unidirectional and during the ship monitoring process, the Yagi-LPDA antenna can be work well seen from the direction of the Yagi-LPDA antenna beam which is in the same direction and focused so as to be able to monitor the presence of ships in Benoa waters, the Lombok Strait and Nusa Penida.